Finite element simulation of magnetic nanoparticles augmented polymeric microcapsules in anaerobic digestion / Saifuddin Zulkeflee, Mohamed Syazwan Osman and Nur Shafieza Azizan - Zulkeflee, Saifuddin; Osman, Mohamed Syazwan; Azizan, Nur Shafieza (2020)
The application of magnetic nanoparticles (MNPs) in anaerobic digestion (AD) had become adverse as it can increase the performance of AD. Nevertheless, the MNPs have a very significant effect to AD as it can inhibit the microbial activities by increasing the iron content thus reduce the performance of AD. This study was conducted to determine the role of MNPs- Polymer microcapsules in anaerobic digestion of sludge. Moreover, it was also conducted to perform the finite element simulation of MNPs-Polymer microcapsules in anaerobic digestion. For the experimental setup, the MNPs-Polymer microcapsules was synthesis by using phase inversion method and the effect MNPs-nanoparticle polymer microcapsules was investigated. The iron oxide (Fe3O4) was used for the nanoparticles while the Polyvinylidene fluoride (PVDF) as the immobilization agent. There will be 3 batches anaerobic digestion setup in which all of the digesters were filled with the same amount of sludge but the Reactor 2 (R2) was added with 2g of MNPs, while Reactor 3 (R3) was added with 58.8g of MNPs-Polymer microcapsules. The result from the experimental indicates that cumulative methane production increased to 7.5% and cumulative carbon dioxide production decreased to 74.38% when MNPs-Polymer microcapsules were introduced to the process. However, from the simulation conducted, the methane production had decrease to 1.09% and the production of carbon dioxide had reduced to only 0.59%. Moreover, for the iron concentration analysis, it had shown that the MNPs-Polymer microcapsules had reduce the iron content by 90.6% from the experimental analysis and 77% from the simulation analysis. Lastly, as for the efficiency of the MNPs-Polymer microcapsules, it can still perform well in anaerobic digestion after 14 days. Lastly, the physico-chemical analysis were performed on both influent and effluent sample of digestates for total suspended solids (TSS), turbidity, pH value, Chemical Oxygen Demand (COD) and Biological Oxygen Demand (BOD).